Evaluating Factors Affecting the Satisfaction of War Tourists in Iran to Make Sustainable Decisions about the Parameters Influencing the Quality of Travel Using the Quality Function Deployment Method - Mohammad Mahdi Mohtadi; Seyedeh Najmeh Motavallizadeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to identify and analyze the factors affecting the satisfaction of war tourists visiting the operational areas of the holy defense in the south of the country through travels of the Path of Light.Methodology: In the first phase of this study, interviews were used to identify factors affecting visitor satisfaction and travel quality. The identified factors affecting visitor satisfaction have been validated using a questionnaire distribution and factor analysis, and finally, based on these criteria and using a performance expansion matrix, the factors affecting the quality of these trips have been ranked.Findings: While identifying a list of factors affecting the satisfaction of tourists and measures affecting the quality of travel, this study showed that the most crucial factor affecting the satisfaction of tourists is that they tend to have more access to entertainment and leisure to enjoy more. The involvement of most other institutions and organizations and the use of their subtleties were also identified as the most critical qualitative factors influencing the research.Originality/Value: The issue of quality management in tourism still needs more scientific attention. Quality science development methods have been able to translate the call of visitors as war tourism customers to understandable concepts for the relevant organizations and help them make appropriate decisions and remain faithful to their choices.